Challenges of Guaranteeing Access to Medicines in Mexico: Lessons from Recent Changes in Pharmaceuticals Procurement - Octavio Gómez-Dantés; Anahi Dreser; Veronika J. Wirtz; Michael R. Reich (Taylor & Francis Group, 2022)
During the last two decades, Mexico adopted policies intended to increase the efficiency and effectiveness of medicines procurement in its nationally fragmented health system. In this policy report, we review Mexico's efforts to guarantee access to medicines during three national administrations (from 2000 to 2018), and then examine major health system changes introduced by the current government (2018-2024), which have created significant setbacks in guaranteeing access to medicines in Mexico. These recent changes are having important consequences in the levels of satisfaction of health care users and citizens, household expenditure on health, and health conditions. We suggest key lessons for Mexico and other countries seeking to improve pharmaceutical procurement as part of guaranteeing access to medicines.